THE STUDY OF MODIFICATION FOR REFORMING UNIT OF AMMONIA PLANT PUSRI 3 AND UTILIZATION OF PRODUCER GAS AS NATURAL GAS FUEL SUBTITUTE IN PT PUPUK SRIWIDJAJA - NIM: 23005005, Junaedi
Abstract: This study dealt with an energy conservation program at the reforming unit in PT PUSRI, to anticipate the increase in price and possible shortage of natural gas in the near future. A potential reduction of natural gas consumption was evaluated based on thermodynamic modeling and simulation. Three process modifications were studied and their performance had been compared to the existing unit: a. KRES (KBR Reforming Exchanger System); totally replace the existingprimary reformer b. ATR (AutoThermal Reformer): totally replace the existing primary reformer c. KRES-revamp: appending KRES on the existing unit In the modeling and simulation, the following targets had been set: H2 production rate and molar ratio of H2/CO. Compared to that of the existing reformer of 37.15 MMBtu/metric ton of NH3, the natural gas consumption in the proposed modified process were lower by 9%, 15% and 20% in KRES-revamp, KRES and ATR respectively. Unfortunately, the proposed modified process produced less steam as by-product due to the decrease in waste sensible heat. Therefore to restore the steam supply, the proposed modified process required an additional auxiliary boiler with a capacity of 105 tons/hour for KRES-revamp, 137 tons/hour for KRES, and 97 tons/hour for ATR. KRES-revamp had been considered as the most attractive modification, since it would still utilize the existing primary reformer. Further simulation on the operation of KRES-revamp showed that maintaining the existing primary reformer throughput and increasing the ammonia production rate due to the appending KRES was not attractive. The best modification was maintaining the ammonia production rate at the original of 1200 MTPD, while reducing the throughput of the existing primary reformer as part of its load would be replaced by KRES. This modification might give an annual natural gas saving of about 8.39%. Beside that, based on investment aspect, KRES-revamp is very attractive with payback period about 10 months.